Efficient Interfacial Solar Steam Generator with Controlled Macromorphology Derived from Flour via "Dough Figurine" Technology. Issue 9 (27th May 2019) - Li, Zhengtong; Wang, Chengbing; Li, Zeyu; Deng, Lin; Su, Jinbu; Shi, Jing; An, Meng
Abstract : A solar‐driven interface steam generator (SISG) has potential applications in saline water desalination and polluted water purification. A shape‐ and size‐controlled, low‐cost, eco‐friendly solar‐absorber material is urgently desired for practical applications of SISGs. Herein, a facile, sustainable, and scalable approach is proposed to produce tailored SISGs with controlled macromorphology derived from flour via "dough figurine" technology originating from the China Han Dynasty. Three kinds of self‐floated flour‐based absorbers, i.e., near‐cylindrical (integrated), near‐spherical (loose packing), and powdery (dense packing) absorber used as SISGs, are discussed. More importantly, it is found that the macromorphology significantly influences water transport and interfacial thermal management of SISGs; thus the integrated absorber has an obvious advantage over the other two absorbers, which possesses a high evaporation efficiency of 71.9% at normal solar illumination. The proposed "dough figurine" technology breaks the limitations of the inherent geometry of reported biomass‐based SISGs, which provides an important guidance for SISG use in remote and impoverished areas. Abstract : Dough figurine, as a traditional Chinese technology, is successfully applied to the molding process of a solar steam generation device. A biomass flour‐based absorber with a common structure (near‐cylindrical) can achieve a high evaporation efficiency of about 71.93% under 1 sun radiation. Different placements of the same materials in the system are also discussed in detail.